"FORMATION OF PROFESSIONAL-AESTHETIC READINESS FOR FUTURE TEACHERS OF FINE ARTS" - Ordasheva, M.Zh.; Plokhotenko, V.N. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The essence and structure of vocational readiness of students of higher pedagogical institutions for the implementation of pedagogical activity is conside-red in the article. The theoretical and methodological foundations of the formation of the professional readiness of students of higher pedagogical universities are described. The main types of readiness are revealed. Generalized requirements for professional and pedagogical training of teachers of fine art are generalized. The definition of professional and aesthetic readiness of future teachers of Fine Arts is given. Three structural components of the professional and aesthetic readiness of the future teacher of Fine Arts for professional activity are singled out.
Keywords: readiness; professional-aesthetic readiness; Fine Arts; teacher; teacher of Fine Arts; students of art faculties of teacher training Universities